FPGA based synchronous multi-channel PWM generator for humanoid robot - Muttaqin, Adharul; Finnadi, Stefanus Dion; Abidin, Zainul; Araki, Kakeru (Institute of Advanced Engineering and Science, 2021)
In this paper, synchronous multi-channel pulse width modulation (PWM) generator for driving servo motors of humanoid robot was proposed. In an application, the humanoid robot requires smooth and beautiful movement, therefore the PWM signal for each servo motor must be synchronized. Since microcontroller (slave) has no enough channels to generate synchronous PWMs for 32 servo motors, field programmable gate array (FPGA) was used as slave for the humanoid robot. The FPGA was controlled by microcontroller (master) using serial communication. Simulation results show the system can perform serial communication, synchronize, and convert data well. The system can also generate PWM simultaneously with accurate duty cycle and fix period of 20ms.